Uberization and elections in Brazil: a ballot box name analysis referring to transport and delivery digital platforms (2016-2020) - Tozi, Fábio (2023)
Transport and delivery digital platforms symbolize the uberisation of labor relations within the capitalist neoliberal phase, and they have become increasingly present in daily life. In order to reveal political-electoral reverberations of such process, this article presents an analysis of candidates’ ballot names considering their Electoral Geography when it comes to the Municipal Elections (2016 and 2020) referring to uberisation. Initially, based on data from the Brazilian Superior Electoral Court (TSE), the growth in the number of these candidates is understood, such as their profile, their distribution across the territory, and political parties. In a second step, it is considered the trajectory of a particular app driver, who has become a public persona, being elected councilor for São Paulo in 2020. Then, it is presented how the national candidate network has articulated based on issues related to drivers' activity by apps. Some final considerations have indicated a considered growth regarding the adoption of ballot names linked to uberisation, this is geographically selective but indicative of a trivialization about this process in social and political life. Besides, there are institutional limits to City Councils actions concerning a national regulated process. Other tensions are also indicated between the public and private sphere stemming from digital platforms in the territory.